2013
DOI: 10.1523/jneurosci.5713-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Novel Flicker-Sensitive Visual Circuit Neurons Inhibited by Stationary Patterns

Abstract: Many animals use visual motion cues for navigating within their surroundings. Both flies and vertebrates compute local motion by temporal correlation of neighboring photoreceptors, via so-called elementary motion detectors (EMDs). In the fly lobula plate and the vertebrate visual cortex the output from many EMDs is pooled in neurons sensitive to wide-field optic flow. Although the EMD has been the preferred model for more than 50 years, recent work has highlighted its limitations in describing some visual beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 61 publications
0
22
0
Order By: Relevance
“…A role for the medulla or lobula in insect visual selective attention is compelling, particularly in light of a number of recent studies on neurons connecting contralateral optic lobes with the central brain in insects (42)(43)(44) have shown that centrifugal feedback neurons also display attention-like properties at a single-cell level (44). Similar long-ranging neurons may be key for inducing the coherent population activity we observe in the medulla and lobula.…”
Section: Discussionmentioning
confidence: 77%
“…A role for the medulla or lobula in insect visual selective attention is compelling, particularly in light of a number of recent studies on neurons connecting contralateral optic lobes with the central brain in insects (42)(43)(44) have shown that centrifugal feedback neurons also display attention-like properties at a single-cell level (44). Similar long-ranging neurons may be key for inducing the coherent population activity we observe in the medulla and lobula.…”
Section: Discussionmentioning
confidence: 77%
“…cSIFE is also inhibited by stationary gratings, regardless of their orientation ( Fig. 1b , N =16) 26 .…”
Section: Resultsmentioning
confidence: 83%
“…As opposed to the more well-studied classic lobula plate tangential cells (LPTCs) that are clearly direction-selective 27 , cSIFE responds strongly to moving sinusoidal gratings, regardless of the direction of motion ( Fig. 1a , N =16) 26 . cSIFE is also inhibited by stationary gratings, regardless of their orientation ( Fig.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations